Active remodeling of capillary endothelium via cancer cell-derived MMP9 promotes metastatic brain colonization - Karreman, Matthia A.; Bauer, Alexander T.; Solecki, Gergely; Bergmeister-Berghoff, Anna Sophie; Mayer, Chanté D.; Frey, Katharina; Hebach, Nils R.; Feinauer, Manuel; Schieber, Nicole L.; Tehranian, Cedric; Mercier, Luc; Singhal, Mahak; et al. (Cancer research, 2023)
Crossing the blood-brain barrier is a crucial, rate-limiting step of brain metastasis. Understanding of the mechanisms of cancer cell extravasation from brain microcapillaries is limited as the underlying cellular and molecular processes cannot be adequately investigated using in vitro models and endpoint in vivo experiments. Using ultrastructural and functional imaging, we demonstrate that dynamic changes of activated brain microcapillaries promote the mandatory first steps of brain colonization. Successful extravasation of arrested cancer cells occurred when adjacent capillary endothelial cells (EC) entered into a distinct remodeling process. After extravasation, capillary loops were formed, which was characteristic of aggressive metastatic growth. Upon cancer cell arrest in brain microcapillaries, matrix-metalloprotease 9 (MMP9) was expressed. Inhibition of MMP2/9 and genetic perturbation of MMP9 in cancer cells, but not the host, reduced EC projections, extravasation, and brain metastasis outgrowth. These findings establish an active role of ECs in the process of cancer cell extravasation, facilitated by cross-talk between the two cell types. This extends our understanding of how host cells can contribute to brain metastasis formation and how to prevent it.Tracking single extravasating cancer cells using multimodal correlative microscopy uncovers a brain seeding mechanism involving endothelial remodeling driven by cancer cell-derived MMP9, which might enable the development of approaches to prevent brain metastasis.